Pengaruh Media Visual Tiga Dimensi terhadap Hasil Belajar Matematika pada Materi Volume Kubus dan Balok Kelas V SD - Efrita Zulaiha; Arrini Shabrina Anshor; Erfiani Humairah (EduInovasi: Journal of Basic Educational Studies, 2024)
This research aims to determine the effect of three-dimensional visual media on mathematics learning outcomes in the volume of cubes and blocks for class V SD Negeri 060877 Medan. The type of research is quantitative research with quasi-experimental methods. The population in the study was all fifth grade students with a total of 45 students. The sample for this research was class VA totaling 22 students as the experimental class and class VB totaling 23 students as the control class. The data collection technique uses a mathematics learning outcomes test. The data analysis technique used is data description, trend testing, requirements testing, and hypothesis testing using the t-test. Based on the results of the t-test, there is a positive and significant influence on three-dimensional visual media on mathematics learning outcomes in the material volume of cubes and blocks for class V SD Negeri 060877 Medan with a value (tcount>ttable) namely (14.33>1.67) on significance level 5 percent. This means that three-dimensional visual media can influence mathematics learning outcomes in the volume of cubes and blocks.